The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18094676
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Framework for Collecting Site-Specific Sampling and Survey Data to Support Analyses of Health Impacts from Land-Based Pollution in Low- and Middle-Income Countries

Abstract: The rise of small-scale and localized economic activities in low- and middle-income countries (LMICs) has led to increased exposures to contaminants associated with these processes and the potential for resulting adverse health effects in exposed communities. Risk assessment is the process of building models to predict the probability of adverse outcomes based on concentration-response functions and exposure scenarios for individual contaminants, while epidemiology uses statistical methods to explore associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…General multiple linear models were used to assess the impact of HFE polymorphisms on Pb body burden, adjusted for age, BMI, exposure duration, alcohol, and smoking. Since we have previously published that consumption of milk and dairy products (MDP) could modulate Pb body burden, we also included this variable in the model: participants were classified as low-MDP intake and high-MDP intake (for details, see Gomes et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General multiple linear models were used to assess the impact of HFE polymorphisms on Pb body burden, adjusted for age, BMI, exposure duration, alcohol, and smoking. Since we have previously published that consumption of milk and dairy products (MDP) could modulate Pb body burden, we also included this variable in the model: participants were classified as low-MDP intake and high-MDP intake (for details, see Gomes et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, general multiple linear models were also applied to assess the impact of HFE polymorphisms on 8-OHdG, as function of BLL and PLL, adjusted for age, BMI, exposure period, alcohol, and smoking. Moreover, we have earlier reported that exposure to Pb is associated with alterations of biochemical parameters of the redox status, such as GSH and GPX, we also included these variables in the model [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%